The investigation of the effects of the sports goalball on the level of some physical propriety of visually handicapped individuals - Ersin Arslan; H. Bayram Temur; İsrafil Aslan; Mahmut Aktı (Türk Spor ve Egzersiz Dergisi)
This study was carried out with the aim of stating whether or not playing goalball is effective on the duration of aural reaction, the power of hand and grasping, flexibility and balance of the individuals those visually disabled in different degrees. For this purpose, in the province Van, 30 experimental subjects were included  in the study, 15 subjects of the study were of  an advancing group whose visual degrees were varied between B1 and B3 and other 15 subjects were of not doing sports . The average age of those subjects was 31.53 ± 9.19. The average age of those doing sport was 2, 93 ± ,88 years. The test of the right and left aural reaction of the subjects was defined with the device New Test 1000. Also, their grasping power was measured with Grip Strength Dynamometer. In addition, the test of flexibility of subjects was applied twice and the highest grade was recorded.  In the hopping test, those completed the test were evaluated with (+), and those not completed the test were evaluated with (-). Then, the digital data was transferred to electronic environment. One way variance analysis Mann –Whitney (One Way) and T Tests were used for statistical analyses of the data.     In conclusion, it was figured out that there isn't any significant difference on account of height, weight, flexibility and hopping test (p Ë‚ 0, 05).  It was assigned that there is a difference (p Ë‚ 0, 01) between the groups in duration of right hand aural reaction and left hand grasping power; there are significant differences between the groups in age, duration of left hand reaction and right hand grasping power.